Influence of donor type, stem cell source and conditioning on outcomes after haploidentical transplant for lymphoma – a LWP‐EBMT study. (9th September 2019) - Bazarbachi, Ali; Boumendil, Ariane; Finel, Hervé; Castagna, Luca; Dominietto, Alida; Blaise, Didier; Diez‐Martin, Jose L.; Tischer, Johanna; Gülbas, Zafer; Wallet, Hélène L.; Corral, Lucia L.; Mohty, Mohamad; et al.
Summary: Haploidentical stem cell transplantation (haploSCT) is becoming a major transplant modality for lymphoma. To assess the effects of donor characteristics, stem cell source and conditioning on outcomes, we identified 474 adults with Hodgkin (HL; 240), peripheral T‐cell (PTCL; 88), diffuse large B‐cell (77), mantle cell (40) or follicular lymphoma (FL; 29), who received haploSCT with post‐transplant cyclophosphamide. Median follow‐up of alive patients was 32 months. On multivariate analysis, acute graft‐versus‐host disease (GVHD) grade 2–4 was lower with offspring donors or bone marrow cells, whereas extensive chronic GVHD was higher in partial response at haploSCT or when using sisters, haploidentical donors beyond first degree, or female donors in male patients. Progression‐free survival (PFS) was better for FL, HL and PTCL, whereas overall survival (OS) was better for HL and PTCL. Complete remission at haploSCT improved PFS and OS whereas these were negatively affected by cytomegalovirus donor positive/recipient positive status. No other donor characteristics (age, gender, human leucocyte antigen mismatch, ABO incompatibility) affected PFS or OS except use of haploidentical donors beyond first degree, which negatively affected OS. PFS and OS are mostly influenced by disease status and lymphoma subtype, supporting the use of any first degree haploidentical family member as a donor.